STT3-dependent PD-L1 accumulation on cancer stem cells promotes immune evasion - Hsu, Jung-Mao; Xia, Weiya; Hsu, Yi-Hsin; Chan, Li-Chuan; Yu, Wen-Hsuan; Cha, Jong-Ho; Chen, Chun-Te; Liao, Hsin-Wei; Kuo, Chu-Wei; Khoo, Kay-Hooi; Hsu, Jennifer L.; Li, Chia-Wei; et al. (Nature communications, 2018)
Enriched PD-L1 expression in cancer stem-like cells (CSCs) contributes to CSC immune evasion. However, the mechanisms underlying PD-L1 enrichment in CSCs remain unclear. Here, we demonstrate that epithelial–mesenchymal transition (EMT) enriches PD-L1 in CSCs by the EMT/β-catenin/STT3/PD-L1 signaling axis, in which EMT transcriptionally induces N-glycosyltransferase STT3 through β-catenin, and subsequent STT3-dependent PD-L1 N-glycosylation stabilizes and upregulates PD-L1. The axis is also utilized by the general cancer cell population, but it has much more profound effect on CSCs as EMT induces more STT3 in CSCs than in non-CSCs. We further identify a non-canonical mesenchymal–epithelial transition (MET) activity of etoposide, which suppresses the EMT/β-catenin/STT3/PD-L1 axis through TOP2B degradation-dependent nuclear β-catenin reduction, leading to PD-L1 downregulation of CSCs and non-CSCs and sensitization of cancer cells to anti-Tim-3 therapy. Together, our results link MET to PD-L1 stabilization through glycosylation regulation and reveal it as a potential strategy to enhance cancer immunotherapy efficacy. PD-L1 accumulates on cancer stem cells and favours immune evasion but the mechanism underlying this accumulation are unknown. Here the authors show that epithelial-mesenchymal transition induces glycosylation and stabilisation of PD-L1; antagonising this process renders cancer cells sensitive to anti-Tim3-therapy.